Drying effects and dry matter losses during seasonal storage of spruce wood chips under practical conditions. (April 2018) - Hofmann, Nicolas; Mendel, Theresa; Schulmeyer, Fabian; Kuptz, Daniel; Borchert, Herbert; Hartmann, Hans
Abstract: The storage of wood chips is important for the biomass supply chain as it compensates for temporal differences in production and consumption. Typical storage-related problems are dry matter and energy losses due to microbial activity. In extensive field trials, we investigated the storage of spruce wood chips from forest residues (FRC) and from energy roundwood (ERC) with and without rain protection under Central European conditions. Additionally, we examined the storage of unchipped piles. The results indicate that the investigated factors, i. e. storage duration, season, assortment and rain protection, have a statistically significant influence on moisture content and dry matter loss of wood chips. During five months of storage, the highest decline in moisture content was 22.6 %-points, the highest dry matter loss 11.1 %. In winter, energy losses reached up to 11.3 %. In summer, energy contents did not change or even increased slightly (max. 4.7 %). Pile temperature and dry matter losses were significantly positively correlated in FRC. Formation of different layers within the piles could be detected. Storage performance was better in unchipped than in chipped energy roundwood. Storage of unchipped forest residues was not beneficial concerning energy content, but fuel quality increased due to reduced ash and fine particle content. Clear best practice recommendations could be drawn regarding wood chip storage under Central European conditions. During winter, FRC should be stored with rain protection or as short as possible while during a dry and warm summer, wood chips can be stored with only few restrictions. Highlights: Storage of forest wood chips and unchipped wood was examined in extensive field trials. Trials were conducted during winter and summer and with and without rain cover. Influencing factors on drying and dry matter loss were detected using factorial ANOVA. Drying can compensate dry matter loss regarding energy content under certain conditions. Storage before chipping can increase quality of wood chips (fine and ash content).